Aqueous MXene/PH1000 Hybrid Inks for Inkjet‐Printing Micro‐Supercapacitors with Unprecedented Volumetric Capacitance and Modular Self‐Powered Microelectronics. Issue 23 (28th April 2021) - Ma, Jiaxin; Zheng, Shuanghao; Cao, Yuexian; Zhu, Yuanyuan; Das, Pratteek; Wang, Hui; Liu, Yu; Wang, Jiemin; Chi, Liping; Liu, Shengzhong (Frank); Wu, Zhong‐Shuai
Abstract: Despite intense development of inkjet printing for scalable and customizable fabrication of power sources, one major shortcoming is the lack of eco‐friendly aqueous inks free of additives (e.g., toxic solvents, surfactants). Here, an aqueous printable MXene/poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonic acid) (MP) hybrid ink is demonstrated that has an adjustable viscosity to directly inkjet‐print micro‐supercapacitors (MP‐MSCs) with excellent performance, seamless integration, and desirable customization, which is crucial for scalable industrialization of self‐powered integrated systems. The MP‐MSCs deliver an unprecedented volumetric capacitance of 754 F cm −3 and a remarkable energy density of 9.4 mWh cm −3, superior to previously reported inkjet‐printed MSCs. Such outstanding performance is partly attributed to highly conductive PH1000 that prevents restacking of MXene nanosheets, enabling fast electron and ion diffusion throughout the microelectrodes. Moreover, MP‐MSCs present exceptional miniaturization and superior modularization featuring high voltage output up to 36 V from 60 serially connected cells and impressive areal voltage of 5.4 V cm −2 connected in tandem. Further, a printable temperature sensor integrated with the MP‐MSC and a flexible solar cell exhibits an exceptional response of 2% and mechanical flexibility without any bias voltage input. Therefore, the MXene inks are expected to create various opportunities for miniaturization and innovative construction of flexible, self‐sustaining, energy harvesting–storing–consuming microsystems for printable electronics. Abstract : A flexible and durable self‐powered integrated system composed of a silicon film solar cell, inkjet‐printed micro‐supercapacitor and a temperature sensor, is demonstrated, where aqueous MXene/MXene/poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonic acid) hybrid inks serve as microelectrodes for micro‐supercapacitors, current collector for temperature sensor, and metal‐free interconnection.